RESPONSIBILITY OF INTERNATIONAL ORGANIZATIONS FOR ACTS CONTRARY TO INTERNATIONAL LAW - Ablakulova Dilfuza Komiljon qizi (International Journal of Literature and Language Studies, 2026)
This paper analyzes international organizations, their international legal status, and their acts contrary to international law through international legal norms and practical examples. The primary objective of the article is to conduct an in-depth analysis of the issue of responsibility of international organizations, using the judicial decisions in the Behrami and Kadi cases as examples. To achieve this objective, the following tasks are defined: a) To determine the significance and status of international organizations in international law; b) To comprehensively analyze the ARIO document and the Convention on the Privileges and Immunities of the United Nations; c) To discuss the forms and types of offenses and responsibility in international law; d) To analyze the Behrami and Saramati, and Kadi court cases in light of legal norms.